1990
DOI: 10.1152/ajpregu.1990.259.5.r1056
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin and oxytocin in rat brain in response to prostaglandin fever

Abstract: Urethan-anesthetized rats were used to identify effective stimuli for the release of the peptides arginine vasopressin (AVP) and oxytocin into the ventral septal area (VSA) of the brain. Febrile responses to intracerebroventricular injection of prostaglandin E1 (PGE1) were observed in rats whose body temperatures were maintained at 35, 37, or 39 degrees C. Microinjection of the AVP antagonist d(CH2)5Tyr(Me)AVP into the VSA enhanced fever only when PGE1 administration was associated with a significant rise in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
23
0
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 0 publications
6
23
0
2
Order By: Relevance
“…However, increases in body core temperature cannot sufficiently explain the AVP response as external heating of the animals to levels even greater than that observed following IL-1i infusion did not prompt significant increases in the release of VSA AVP. This observation agrees with an earlier study which also showed that external heating of urethaneanaesthetized rats fails to affect ventral septal AVP levels (Landgraf et al 1990 (Farrar, Kilian, Ruff, Hill & Pert, 1987) (Takao, Newton & De Souza, 1993). Further experiments utilizing IL-1 receptor blockade (both type I and II) are necessary to resolve this issue.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, increases in body core temperature cannot sufficiently explain the AVP response as external heating of the animals to levels even greater than that observed following IL-1i infusion did not prompt significant increases in the release of VSA AVP. This observation agrees with an earlier study which also showed that external heating of urethaneanaesthetized rats fails to affect ventral septal AVP levels (Landgraf et al 1990 (Farrar, Kilian, Ruff, Hill & Pert, 1987) (Takao, Newton & De Souza, 1993). Further experiments utilizing IL-1 receptor blockade (both type I and II) are necessary to resolve this issue.…”
Section: Discussionsupporting
confidence: 90%
“…Mean basal AVP values were within the range observed in previous studies (Landgraf et al 1990;Wilkinson & Kasting, 1993). Administration of PBS into the BST (Fig.…”
Section: Resultssupporting
confidence: 85%
“…However, the relative release of AVP and OT depends on the specific stressor applied (4 -6). Two decades ago it was considered that OT but not AVP was a stress hormone in the rat (7,8). This has since been modified, but controversies about the AVP response to different stressors still exist.…”
Section: Introductionmentioning
confidence: 99%
“…While fever suppression during late pregnancy has yet to be shown in rats, our results from the VSA suggest that endogenous AVP released within this area could similarly be involved in the protection of pregnant rats against fever. In this context, the OXT released within the VSA of pregnant rats may also be involved in fever protection [3,5]. The exact stimuli for the increased release of septal AVP and OXT are not known, but they could involve the pregnancy-related changes in steroid levels [29] which are known to influence AVP and OXT neurons [9,[30][31][32], Parturition is associated with a significantly elevated release of OXT, but not AVP, from the posterior pituitary [33, 34], Pre viously, it was shown that parturition in the sheep is accompa nied by increased release of OXT in the olfactory bulb and substantia nigra [14].…”
mentioning
confidence: 99%
“…Exoge nously applied or endogenously released AVP binds to VI type receptors within the ventral septal area (VSA) of the brain, re sulting in activation of heat loss mechanisms and a reduction in the duration and height of fever [1,2], During prostaglandin-Ei-induced fever, endogenous AVP is released within the VSA [3] from neurons whose cell bodies are situated within the bed nucleus of the stria terminalis; the activity of these neurons appears to be enhanced during experimental fever [4], Inter ference with the action or release of AVP from this vasopressinergic pathway results in enhanced, prolonged fever [2], While a role for endogenous oxytocin (OXT) in fever and antipyresis has not been established, it is of interest that this peptide in released into the VSA both during fever and during passive increases in deep body temperature [3]. There is also evidence that OXT may act in concert with AVP to affect ther moregulatory and other central actions of AVP [5][6][7].…”
mentioning
confidence: 99%